2015
DOI: 10.1080/1461670x.2015.1065197
|View full text |Cite
|
Sign up to set email alerts
|

Times Are a Changin’

Abstract: This study offers an ethnographic analysis of the merger of the digitally native news nonprofit the St. Louis Beacon and St. Louis Public Radio. Researchers observed news work and interviewed journalists before and after the merger, paying close attention to how routines shifted subsequently. Through the lens of gatekeeping theory, researchers discuss how new specialized roles, technical changes, and shifting news judgments affected communication routines, and how journalists did their jobs. These findings are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Prolonged stress is commonplace among journalists, and an expected consequence of the career; however, organizational research in newsrooms has shown that asking journalists to take on additional, unfamiliar work adds stress and depletes coping mechanisms (Reinardy, 2013). For example, in a study of a newsroom merger between a newspaper and a radio station, Ferrucci et al (2017) found that the shifting of news gathering routines, expectations, and job roles, and the introduction of new technology, dramatically increased newsroom stress. Furthermore, if those changes are overly complex or incompatible with other demands, such as requiring the use of new technology, or changing the focus of coverage, the stress can be even worse (Ekdale et al, 2015a).…”
Section: Stress and Work Commitmentmentioning
confidence: 99%
“…Prolonged stress is commonplace among journalists, and an expected consequence of the career; however, organizational research in newsrooms has shown that asking journalists to take on additional, unfamiliar work adds stress and depletes coping mechanisms (Reinardy, 2013). For example, in a study of a newsroom merger between a newspaper and a radio station, Ferrucci et al (2017) found that the shifting of news gathering routines, expectations, and job roles, and the introduction of new technology, dramatically increased newsroom stress. Furthermore, if those changes are overly complex or incompatible with other demands, such as requiring the use of new technology, or changing the focus of coverage, the stress can be even worse (Ekdale et al, 2015a).…”
Section: Stress and Work Commitmentmentioning
confidence: 99%
“…With ownership as a deciding characteristic in determining market orientation, an organization that does not compete in either the stock market or the advertising market qualifies as weakly market oriented (Ferrucci, 2018b; Konieczna & Robinson, 2014). While even the most weakly market-oriented news organization would still be market oriented in some ways (Beam, 2003), a nonprofit would not have to cater to ownership and would then be overseen by very different leadership compared to for-profit news organizations (Ferrucci, 2015a, 2017a, 2018b; Ferrucci, Russell, Choi, Duffy, & Thorson, 2017). Therefore, a nonprofit news organization that does not run advertising is considered weakly market oriented for this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The tensions involved frequently revolve around identity and boundaries, as collaboration highlights the extent to which different actors can influence both conceptual definitions of news and journalistic practice itself. Previous research on collaborative efforts has explored the varying degrees to which organizations do or do not work together in the planning, creation and distribution of news coverage (Anderson, 2013;Benson, 2017;Ferrucci et al, 2017;Lewis & Usher, 2016;Lowery, 2005). This project aims to take the next step and focus on the priorities and values imbued in those processes, especially how non-journalistic partners influence the ways these groups characterize their core mission.…”
Section: Collaboration Boundaries and Reciprocal Journalismmentioning
confidence: 99%